Real-Time Data Processing Pipelines: Enhancing Decision Intelligence with Apache Spark and Kafka - Nishitha Reddy Nalla (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In this era of data-driven workflows, the need for real-time data processing and analysis is essential to stay competitive. The explosion in the amount of data generated and the requirement for actions to be taken as quickly as possible has led organizations to adopt a real-time data processing pipeline. In this paper, we discuss how Apache Spark and Kafka are modern big data technologies promoting decision intelligence by means of building fast data-processing pipelines. We cover the following topics in this article; Apache Spark and Kafka integrations, Stream Processing, Concepts, challenges and best practices for implementing real time data pipelines. They outline the implications and practical applications for developers working with these cutting-edge technologies, alongside case studies across different sectors including finance, healthcare, and e-commerce.